2003
DOI: 10.1021/jo034780g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 17-α-Substituted Estradiol-Pyridin-2-yl Hydrazine Conjugates as Effective Ligands for Labeling with Alberto's Complex fac-[Re(OH2)3(CO)3]+ in Water

Abstract: The development of (99m)Tc-estradiol radiopharmaceuticals would be advantageous for the detection of estrogen receptor-positive breast tumors. Estradiol derivatives conjugated to organometallic tricarbonyl-Tc(I) and related Re(I) complexes are capable of achieving high receptor binding affinity, but effective methods for synthesizing radiolabeled complexes in water are not available. Our interest in the synthesis of 2-hydrazinopyridines as ligands for Tc and Re led us to investigate Pd-catalyzed amination reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 117 publications
0
22
0
Order By: Relevance
“…Conjugates involving metal-carbonyl complexes and estrogen derivatives are reported in the literature 45,46,60,[65][66][67] but, as far as we know, they were never used for infrared imaging. We previously showed that the rhenium tris-carbonyl moiety was reliable for sub-cellular IR-imaging 5,11 using the strong infrared absorptions of CO stretching (E and A 1 -bands in C 3v symmetry, respectively at 1915 cm À1 and 2025 cm À1 ).…”
Section: Synthesis and Characterization Ofmentioning
confidence: 99%
“…Conjugates involving metal-carbonyl complexes and estrogen derivatives are reported in the literature 45,46,60,[65][66][67] but, as far as we know, they were never used for infrared imaging. We previously showed that the rhenium tris-carbonyl moiety was reliable for sub-cellular IR-imaging 5,11 using the strong infrared absorptions of CO stretching (E and A 1 -bands in C 3v symmetry, respectively at 1915 cm À1 and 2025 cm À1 ).…”
Section: Synthesis and Characterization Ofmentioning
confidence: 99%
“…One key advantage of technetium comes from its rich chemical behavior that can assume a large spectrum of structural arrangements, the most important being the [Tc(CO) 3 ] + (carbonyl), [TcN] 2+ (nitrido), and [ReTcO] 3+ (oxo) cores (Arterburn, Corona, Rao, Carlson, & Katzenellenbogen, ; Mull, Sattigeri, Rodriguez, & Katzenellenbogen, ; Neto et al, ; Takahashi et al, ; Wüst, Spies, & Johannsen, ; Xia et al, ). The selection of the adequate combination of metal core and chelator is essential to allow a fine‐tuning of the physicochemical and biological properties of the resulting radiopharmaceutical (Bandoli, Dolmella, Porchia, Refosco, & Tisato, ; Bolzati et al, ; Pasqualini & Duatti, ).…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Apart from material science, the construction of aryl alkynes plays an important role in the synthesis of complex molecules of pharmaceutical and agrochemical interest (e.g. 5, [5] 6, [6] 7 [7] ), even though the arylene-ethynylene structure itself does not often occur in natural products, which is in marked contrast to the corresponding vinylene-ethynylene motif. [8] However, the alkynylation of aromatic halides and subsequent cyclization is a widely used method for the synthesis of carbo- [9] and heterocycles [10] as well as intermediates of natural products.…”
mentioning
confidence: 99%